Efficacy of a 4-Food Elimination Diet for Children With Eosinophilic Esophagitis - Kagalwalla, Amir F.; Wechsler, Joshua B.; Amsden, Katie; Schwartz, Sally; Makhija, Melanie; Olive, Anthony; Davis, Carla M.; Manuel-Rubio, Maria; Marcus, Seth; Shaykin, Ronda; Sulkowski, Maureen; Johnson, Kristen; et al. (Clinical gastroenterology and hepatology, 2017)
A 6-food elimination diet induces remission in most children and adults with eosinophilic esophagitis (EoE). The effectiveness of empiric elimination of only 4 foods has not been studied in children. We performed a prospective observational outcome study in children with EoE treated with dietary exclusion of cow's milk, wheat, egg, and soy. The objective was to assess the clinical, endoscopic, and histologic efficacy of this treatment in EoE. We recruited children (1–18 years old, diagnosed per consensus guidelines) from 4 medical centers. Study participants (n = 78) were given a proton pump inhibitor twice daily and underwent a baseline esophagogastroduodenoscopy. Subjects were instructed on dietary exclusion of cow's milk, wheat, egg, and soy. Clinical, endoscopic, and histologic assessments were made after 8 weeks. Responders had single foods reintroduced for 8 weeks, with repeat endoscopy to assess for recurrence of active disease. The primary endpoint was histologic remission (fewer than 15 eosinophils per high-powered field). Secondary endpoints included symptom and endoscopic improvements and identification of foods associated with active histologic disease. After 8 weeks on 4-food elimination diet, 50 subjects were in histologic remission (64%). The subjects' mean baseline clinical symptoms score was 4.5, which decreased to 2.3 after 8 weeks of 4-food elimination diet (P < .001). The mean endoscopic baseline score was 2.1, which decreased to 1.3 (P < .001). After food reintroduction, the most common food triggers that induced histologic inflammation were cow's milk (85%), egg (35%), wheat (33%), and soy (19%). One food trigger that induced recurrence of esophageal inflammation was identified in 62% of patients and cow's milk–induced EoE was present in 88% of these patients. In a prospective study of children with EoE, 8 weeks of 4-food elimination diet induced clinical, endoscopic, and histologic remission in more than 60% of children with EoE. Although less restrictive than 6-food elimination diet, 4-food elimination diet was nearly as effective, and can be recommended as a treatment for children with EoE.